Paleocene initial indentation and early growth of the Pamir as recorded in the western Tarim Basin - Zhang, Shijie; Hu, Xiumian; Garzanti, Eduardo (Tectonophysics, 2019)
•The initial uplift, indentation, and northward growth of the Pamir began in the Paleocene.•A major provenance change in the western Tarim Basin took place in the early Paleogene.•West Kunlun mountains separated the Tarim and Central Pamir-Aksai Chin basins in the Jurassic-Cretaceous. It is presently unclear as to when and how the Pamir were uplifted to their current elevation, because a Cenozoic sedimentary record is lacking on the Pamir Plateau, and the Pamir domes only record metamorphism associated with crustal shortening since ∼37 Ma. Studies of the tectonic and geomorphological evolution of the Pamir in the early stages of the India–Asia continental collision are also lacking. The western Tarim Basin at the northeastern margin of the Pamir provides an ideal opportunity to investigate their formation and evolution. Four Cretaceous–Paleogene stratigraphic sections were examined in this study. From these, we infer that the West Kunlun Mountains were topographic highs during the Mesozoic that divided the adjacent Central Pamir–Tianshuihai terrane from the Tarim Basin. This paleo-topographic configuration lasted until a marine transgression occurred in the Aksai Chin and Central Pamir areas in the latest Cretaceous. Provenance analysis indicates that sediments in the western Tarim Basin were derived solely from the West Kunlun Mountains until the Paleocene. The appearance of Pamir-derived detrital zircons in Paleocene and Eocene strata of the Tarim Basin suggests that the Pamir was experiencing uplift and reached an elevation similar to, or even higher, than the West Kunlun Mountains. At that time, the sandstone composition documents a provenance change from a stable continental block to an active thrust belt of the proto-West Kunlun Mountains, indicating that the western Tarim Basin evolved from an intraplate to a foreland basin setting. During the Paleocene, alluvial fan conglomerates were deposited along the northeastern margin of the Pamir, and a thick gypsum unit began to be deposited in the Tarim Basin. All these lines of evidence indicate that the north-verging thrusting, foreland basin subsidence, uplift, and northward indentation of the Pamir began in the Paleocene (62–58 Ma).